Evolutionary dissection of monkeypox virus: Positive Darwinian selection drives the adaptation of virus–host interaction proteins - Zhan, Xiao-Yong; Zha, Gao-Feng; He, Yulong (Frontiers in Cellular and Infection Microbiology, 2023)
The emerging and ongoing outbreak of human monkeypox (hMPX) in 2022 is a serious global threat. An understanding of the evolution of the monkeypox virus (MPXV) at the single-gene level may provide clues for exploring the unique aspects of the current outbreak: rapidly expanding and sustained human-to-human transmission. For the current investigation, alleles of 156 MPXV coding genes (which account for >95% of the genomic sequence) have been gathered from roughly 1,500 isolates, including those responsible for the previous outbreaks. Using a range of molecular evolution approaches, we demonstrated that intra-species homologous recombination has a negligible effect on MPXV evolution. Despite the fact that the majority of the MPXV genes (64.10%) were subjected to negative selection at the whole gene level, 10 MPXV coding genes (MPXVgp004, 010, 012, 014, 044, 098, 138, 178, 188, and 191) were found to have a total of 15 codons or amino acid sites that are known to evolve under positive Darwinian selection. Except for MPXVgp138, almost all of these genes encode proteins that interact with the host. Of these, five ankyrin proteins (MPXVgp004, 010, 012, 178, and 188) and one Bcl-2-like protein (MPXVgp014) are involved in poxviruses’ host range determination. We discovered that the majority (80%) of positive amino acid substitutions emerged several decades ago, indicating that these sites have been under constant selection pressure and that more adaptable alleles have been circulating in the natural reservoir. This finding was also supported by the minimum spanning networks of the gene alleles. The three positive amino acid substitutions (T/A426V in MPXVgp010, A423D in MPXVgp012, and S105L in MPXVgp191) appeared in 2019 or 2022, indicating that they would be crucial for the virus’ eventual adaptation to humans. Protein modeling suggests that positive amino acid substitutions may affect protein functions in a variety of ways. Further study should focus on revealing the biological effects of positive amino acid substitutions in the genes for viral adaptation to humans, virulence, transmission, and so on. Our study advances knowledge of MPXV’s adaptive mechanism and provides insights for exploring factors that are responsible for the unique aspects of the current outbreak.